The influence of social media on Saudi graduate students: an explanatory case study of six Saudi graduate students studying in American universities - Alhamadi, Asma Abdulmana (Kansas State University, 2017)
The purpose of this qualitative multiple participant case study was to identify the influence of social media on Saudi graduate students who are active social media users. Social media have been influencing Saudi students differently than those in other socio-cultural contexts due to the uniqueness of the Kingdom of Saudi Arabia (KSA) in terms of cultural, political, economic, and social life. This study contributes to educational technology broadly and understanding the experiences of Saudi graduate students who are active social media users specifically. This study sought to illuminate and clarify understanding of the influence of social media use on graduate students in the KSA. This study investigated the influence of social media on Saudi graduate students through the experience of six Saudi graduate students who have 200K or more followers/subscribers on YouTube, Twitter, Instagram, or Snapchat. Vygotsky-based social constructivism was used to analyze and interpret the findings of the research in an effort to understand and make sense of the impact of social media on education through the participants’ experiences as graduate students and active social media users. The significant findings of this research support social constructivism, in that learning occur through social interaction with the More Knowledgeable Other (MKO) in the Zone of Proximal Development (ZPD). The findings of the study included three emerging themes: (1) social media experience, (2) social media influence, and (3) changes brought by social media. Two categories emerged from the data under the first theme. The categories are (a) planned versus unplanned fame, and (b) social media preferred sites, activities and topics. Three categories and two sub-categories emerged from the second theme: (a) educational influence, which has two sub-categories —(i) formal teaching and learning (ii) informal learning —; (b) financial influence; and (c) gender issues in social media. The results contribute to the limited qualitative research on Saudi graduate students and social media and to the overall social constructivism research in the KSA higher education.
Keywords: Graduate students; Active social media users; Social constructivismSocial media